"I think we need to empower people to manage it better themselves": A qualitative interview study exploring UK healthcare practitioners' perspectives on treating young adults following a sport-related knee injury. (March 2021) - Watkins, Ross; Young, Georgina; Western, Max; Stokes, Keith; McKay, Carly
Abstract: Objectives: To elicit healthcare practitioners' views on treatment following sport-related knee injury in young adults (18–35) and the potential for individuals to self-manage joint health. Design: Semi-structured interviews were audio-recorded, transcribed and analysed systematically using an inductive approach. Setting: South West UK. Participants: Twelve healthcare practitioners with experience of treating young adults. Main outcome measures: Understanding how healthcare practitioners treat young adults following knee injury and to what extent individuals may be able to self-manage knee health. Results: Participants' perceptions were encapsulated in three consistent themes: [1] Treating patients; [2] Maintaining physical activity; and [3] Education and support. All participants described how staying physically active and maintaining a healthy weight were integral to conserving knee health, and that post-injury education was necessary to "empower" patients to self-manage knee health. A need for greater access to support, advice and guidance for patients was also articulated. Conclusions: Healthcare practitioners should tailor their treatment to young adults to account for individual characteristics, aspirations for sport and exercise participation, and their emotional wellbeing. Fulfilment of individuals' educational and supportive needs is key to the establishment of self-management behaviours that may help to conserve knee health. Highlights: Knee health post-injury may be contingent upon tailored treatment that fulfils patients' informational and supportive needs. Our findings support the need for self-management strategies and techniques to address knee health following injury. ·Digital technology could supplement healthcare to enable users to conserve knee health and improve quality of life.